2023
DOI: 10.3390/antiox12010176
|View full text |Cite
|
Sign up to set email alerts
|

Vitiligo and Mental Health: Natural Compounds’ Usefulness

Abstract: Vitiligo is an autoimmune dermatosis frequently associated with other comorbidities, such as mental health disorders. It is unclear if vitiligo triggers mental disorders or if mental disorders trigger vitiligo, but each one affects and worsen the other, if present at the same time. Both mental health disorders and vitiligo present a multifactorial pathogenesis and often require prolonged periods of therapy, sometimes with poor results. Given the possible link of common pathogenetic factors and the need of inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 85 publications
0
6
0
Order By: Relevance
“…Instead, recent studies shed new light on the possibility of contributing to the stress, psychological and genetic factors in such diseases [25,34,35]. Indeed, stressful events and psychological disorders have shown to have a role in the onset and aggravation of vitiligo [35,36]. This was evident during this study when the vitiligo patients were asked if they were been exposed to psychological disorders or suffered from any hereditary problems during their livelihood.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Instead, recent studies shed new light on the possibility of contributing to the stress, psychological and genetic factors in such diseases [25,34,35]. Indeed, stressful events and psychological disorders have shown to have a role in the onset and aggravation of vitiligo [35,36]. This was evident during this study when the vitiligo patients were asked if they were been exposed to psychological disorders or suffered from any hereditary problems during their livelihood.…”
Section: Discussionmentioning
confidence: 94%
“…Actually, many dermatological diseases were shown to be linked to blood types and hence it was envisaged that producing antimelanocyte antibodies in vitiligo would be likely triggered by blood type alloantigens [20,33]. Instead, recent studies shed new light on the possibility of contributing to the stress, psychological and genetic factors in such diseases [25,34,35]. Indeed, stressful events and psychological disorders have shown to have a role in the onset and aggravation of vitiligo [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings appear to diverge from the majority of prior observational investigations. Numerous previous studies on the mental health status of vitiligo patients have consistently demonstrated that, in comparison to the general population, vitiligo patients are more likely to experience mental disorders, such as schizophrenia, depression and anxiety, as well as higher rates of hospitalization and costs for inpatient care for all varieties of psychological disorders 5,7,8,31 . Besides, in case–control research conducted by Liu et al., it was shown that 204 (49.5%) of the 409 patients experienced insomnia 32 .…”
Section: Discussionmentioning
confidence: 98%
“…Numerous previous studies on the mental health status of vitiligo patients have consistently demonstrated that, in comparison to the general population, vitiligo patients are more likely to experience mental disorders, such as schizophrenia, depression and anxiety, as well as higher rates of hospitalization and costs for inpatient care for all varieties of psychological disorders. 5,7,8,31 Besides, in case-control research conducted by Liu et al, it was shown that 204 (49.5%) of the 409 patients experienced insomnia. 32 Nevertheless, utilizing genetic variants as instrumental variables, MR analysis enables the elucidation of the true causality between vitiligo and mental disorders while mitigating the influence of confounding factors.…”
Section: Ta B L Ementioning
confidence: 98%
“…The term “nutraceutical”, formed by combining the words “nutrition” and “pharmaceuticals”, is known as any natural compound derived from food or part of it that provides a medical advantage [ 12 ]. Studies have shown that some of these natural extracts may exert anti-inflammatory, antioxidant, and antiproliferative effects [ 13 ], demonstrating their possible use for the treatment of different cutaneous diseases [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%